SITUACIÓN DE LA PARASITOSIS HEPATOINTESTINAL HUMANA EN EL PERÚ MEDIANTE COPROMICROSCOPIA - Moromi N., Hilda (2000)
In an analitic study of the Parasitology and microbiology and the Peruvian Parasitology congresses and many national publications about, of the last 25 years, it has been abstracted prevalence ciphers of the parasitic diseases in the human intestinal-hepatic segment, that had been taken using the microscopic-fecal test. Using this test, we could obtain 31306 samples, principally of students from: the urban, suburb and rural areas, in almost all over the country. It could be found the following average ciphers: 27.4% (with limits between 0.5-95.0) for nematodes (Ascaris, Trichuris, Uncinarias: Necator orancylostoina, Strongyloides, Enterobius); 6.1% (with limits between 0.2-50.0) for cestodes (Taenia, Hymenolepis, Diphyllobothrium); 6.8% (with limits between 0.3-17.9) for Fasciola; and 17.4% (with limits between 0.3-58.1) forprotozoa (Entamoeba, Giardia, Endolimax, Balantidium, Chilomastix, Iodamoeba, Blastocystis, Cryptosporidium, Cyclospora). With this registered information, we conclude to propose the necesity of improve prevention and control programs for this parasites.